ADAMTS13 gene variants and function in women with preeclampsia: A population- based nested case- control study from the HUNT Study. Issue 2 (August 2015) - von Krogh, Anne-Sophie; Kremer Hovinga, Johanna A.; Romundstad, Pål R.; Roten, Linda T.; Lämmle, Bernhard; Waage, Anders; Quist-Paulsen, Petter
Abstract: Introduction: Known genetic variants with reference to preeclampsia only explain a proportion of the heritable contribution to the development of this condition. The association between preeclampsia and the risk of cardiovascular disease later in life has encouraged the study of genetic variants important in thrombosis and vascular inflammation also in relation to preeclampsia. The von Willebrand factor-cleaving protease, ADAMTS13, plays an important role in micro vascular thrombosis, and partial deficiencies of this enzyme have been observed in association with cardiovascular disease and preeclampsia. However, it remains unknown whether decreased ADAMTS13 levels represent a cause or an effect of the event in placental and cardiovascular disease. Methods: We studied the distribution of three functional genetic variants of ADAMTS13, c.1852C > G (rs28647808), c.4143_4144dupA (rs387906343), and c.3178C > T (rs142572218) in women with preeclampsia and their controls in a nested case–control study from the second Nord-Trøndelag Health Study (HUNT2). We also studied the association between ADAMTS13 activity and preeclampsia, in serum samples procured unrelated in time of the preeclamptic pregnancy. Results: No differences were observed in genotype, allele or haplotype frequencies of the different ADAMTS13 variants when comparing cases and controls, and no association to preeclampsia was found with lower levels of ADAMTS13 activity. Conclusion: Our findings indicate that ADAMTS13 variants and ADAMTS13 activity do not contribute to an increased risk of preeclampsia in the general population. Highlights: We study functional ADAMTS13 variants in relation to preeclampsia This is done in a large, nested case–control study We find no association to preeclampsia (PE) Likewise, no association is found between ADAMTS13 activity and PE